Ring melanoma - Szuścik, Iwona; Romanowska-Dixon, Bożena; Jakubowska, Barbara; Orłowska-Heitzman, Jolanta (Klinika Oczna / Acta Ophthalmologica Polonica, 2008)
Purpose: To describe five cases of ring melanoma. Material and methods: There were 5 patients diagnosed with ring melanoma in Department of Ophthalmology and Ocular Oncology in Krakow between 2001-2007. The preliminary diagnosis was based on a clinical examination and ultrasound biomicroscopy and in 3 cases open biopsy was performed. Results: Ring melanoma in 5 patients at the age between 48-73 were recognized. Four patients were using glaucoma medications. All patients were qualified for enucleation . Conclusion: Ring melanoma is rare wariant of uveal melanoma. It offen masquerades as unilateral glaucoma, and can be difficult to recognize.